Biomolecules - Devasena, T (2010 MJP Publisher, 2010)
Introduction Cell Biology Nucleic Acid Proteins Enzymes Carbohydrates Lipids Electron Transport Chain and Oxidative Phosphorylation Water Vitamins Glossary References Index.
Glossary 253-258p.; References 259-260p. and Index 261-264p.
Keywords: Biomolecules; Chemistry; Nano science